2003
DOI: 10.1093/ajcn/77.6.1459
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of soybean isoflavones from aglycone and glucoside forms in American women

Abstract: The apparent bioavailability of genistein and daidzein is not different when consumed as either aglycone or glucoside by American women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
241
2
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(259 citation statements)
references
References 31 publications
7
241
2
9
Order By: Relevance
“…On the other hand, the decline in urinary isoflavone excretion levels could also result from a longer time period between urine collection and soy food consumption. For example, if soy foods were initially consumed in the evening and during later weeks in the morning, the overnight urine samples would contain fewer isoflavones due to the short half-life of these compounds (Franke et al, 1998a;Setchell et al, 2003;Zubik & Meydani, 2003). Furthermore, the declining trend of urinary isoflavone excretion levels might also reflect a decreasing bioavailability during continuous exposure (Lu et al, 1996).…”
Section: Soy Consumptionmentioning
confidence: 99%
“…On the other hand, the decline in urinary isoflavone excretion levels could also result from a longer time period between urine collection and soy food consumption. For example, if soy foods were initially consumed in the evening and during later weeks in the morning, the overnight urine samples would contain fewer isoflavones due to the short half-life of these compounds (Franke et al, 1998a;Setchell et al, 2003;Zubik & Meydani, 2003). Furthermore, the declining trend of urinary isoflavone excretion levels might also reflect a decreasing bioavailability during continuous exposure (Lu et al, 1996).…”
Section: Soy Consumptionmentioning
confidence: 99%
“…15) Study has also shown no difference in bioavailability between glycoside-form isoflavones and their aglycones. 16) Health effects of daidzin have been proved on memory impairment, hepatic failure, and glucose homeostasis. [17][18][19] It was also reported that glycitin has preventive effect on bone loss and osteonecrosis.…”
mentioning
confidence: 99%
“…Urinary isoflavonoid excretion shows the highest correlation with recent soy intake owing to the fast pharmacokinetics of isoflavonoids (Setchell et al, 2003;Zubik and Meydani, 2003). However, studies with large sample sizes that used validated diet questionnaires have consistently demonstrated significant associations in Asian and Western populations, even when urine was collected only once and soy intake was assessed over the previous year (Maskarinec et al, 1998;Seow et al, 1998;Chen et al, 1999;Atkinson et al, 2002).…”
Section: Discussionmentioning
confidence: 99%